2011
DOI: 10.1177/1350650111398313
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the occurrence of galling during hot forming of Al–Si-coated high-strength steel

Abstract: Galling is a severe form of adhesive wear associated with both cold and hot metal forming operations. In hot sheet metal forming of Al-Si-coated ultrahigh-strength steel (UHSS), transfer occurs from the coated UHSS to the tool surface. This leads to poor quality of produced parts, damage of expensive tooling, and increased downtime for maintenance of the tools. This study thus aims at identifying the salient mechanism(s), which give rise to initiation/occurrence of galling at elevated temperatures. This has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 11 publications
5
43
0
Order By: Relevance
“…Groche and Christiany 21 studied the wear behavior of DP980 sheets formed by different tool materials under strip drawing test with drawbead geometry and observed that wear development was interdependent with surface roughness, temperature, and tension force. The temperature effect was also observed by Hardell et al [22][23][24] in the reciprocating friction tests of Al-Si-coated high strength steel against different tool steels at elevated temperatures, which showed that friction and wear were temperature dependent. The work of Sresomroeng et al 25 showed that CrN film coating on SKD11 tool was effective in friction reduction of sliding against SPFC 980 Y materials based on the scratch, ball-ondisc, and deep drawing tests.…”
Section: Introductionsupporting
confidence: 59%
“…Groche and Christiany 21 studied the wear behavior of DP980 sheets formed by different tool materials under strip drawing test with drawbead geometry and observed that wear development was interdependent with surface roughness, temperature, and tension force. The temperature effect was also observed by Hardell et al [22][23][24] in the reciprocating friction tests of Al-Si-coated high strength steel against different tool steels at elevated temperatures, which showed that friction and wear were temperature dependent. The work of Sresomroeng et al 25 showed that CrN film coating on SKD11 tool was effective in friction reduction of sliding against SPFC 980 Y materials based on the scratch, ball-ondisc, and deep drawing tests.…”
Section: Introductionsupporting
confidence: 59%
“…Al-Si coating is usually applied on high strength steel sheets to eliminate such problem. Hardell et al investigated the tribological characteristics of Al-Si coated high strength steel against different tool steels at temperatures up to 800 °C [7,[34][35][36]56]. This research group observed that Al-Si coating reduced friction at elevated temperatures.…”
Section: Tribological Effect Of Surface Coatings At Elevated Temperatmentioning
confidence: 99%
“…Recently, several research groups have carried out studies to understand friction and wear occurring in hot forming. Pelcastre et al investigated the initiation of galling in hot sheet metal forming of Al-Si-coated ultrahigh-strength steel [7]. Kondratiuk and Kuhn evaluated the Al-Si and Zn-Ni coatings in the hot strip drawing experiments [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some researches on tribology and wear tests devoted to conventional hot stamping of Al-Si coated boron steel sheets are available in literature. Pelcastre et al [15] investigated the mechanism of galling at elevated temperatures during hot stamping of Al-Si coated boron steel sheets by analyzing the behaviour of the actual hot forming tools. Kondratiuk et al [16] performed sheet forming tests to study the wear mechanism by analyzing the tools used to produce a rotationally symmetrical cup.…”
Section: Introductionmentioning
confidence: 99%